LAW ENFORCEMENT AGAINST THE ABUSE OF NARCOTICS TRAFFICING AMONG THE YOUNGER GENERATION - Nugraha Manuella Meliala; Ismaidar (International Conference on Health Science, Green Economics, Educational Review and Technology, 2023)
The problem of drug abuse has broad and complex dimensions, both from a medical, psychiatric, mental health and psychosocial perspective. Drug users can damage the order of family life, the community environment and the school environment, and even directly or indirectly pose a threat to the continuity of development and the future of the Indonesian nation and state. Facing the problem of drug abuse and illicit trafficking requires the government to think about how to deal with this problem, finally the government issued a law. Drug abuse has broad and complex dimensions, both from a medical, psychiatric, mental health and psychosocial perspective. The law is an effective tool to protect people from actions that endanger themselves, such as illicit trafficking and narcotics abuse. The circulation of narcotics among teenagers is influenced by internal and external factors. Psychologically, adolescent behavior is still unstable so they are still easily influenced by the surrounding environment.